Primary Hyperoxaluria Type 1 Disease Manifestations and Healthcare Utilization: A Multi-Country, Online, Chart Review Study - Wang, Xiangling; Danese, David; Brown, Thomas; Baldwin, Jessica; Sajeev, Gautam; Cook, Erin E.; Wang, Yao; Xu, Chunyi; Yang, Hongbo; Moritz, Michael L. (Frontiers in Medicine, 2021)
Background: Primary hyperoxaluria type 1 (PH1) is a rare genetic disease that can result in irreversible damage to the kidneys and, eventually, extrarenal organs. While kidney failure is a known consequence of PH1, few studies to date have characterized clinical consequences of PH1 prior to kidney failure, and data on healthcare resource use outcomes across different stages of disease severity in PH1 are also limited. To help fill this knowledge gap, this study characterized the clinical and healthcare resource use (HRU) burden in patients with PH1 with varying stages of kidney disease. Methods: Nephrologists in the United States, Canada, United Kingdom, France, Germany, and Italy abstracted chart data from patients with PH1 under their care via an online questionnaire. Eligible patients had confirmed PH1 and ≥2 office visits from 2016-2019. Results: A total of 120 patients were analyzed (median age at diagnosis, 17.4 years old, median age at index 19.5 years old, median eGFR at index 45 ml/min/1.73m2; median follow-up 1.7 years). During follow-up, the most common PH1 manifestations were kidney stones and urinary tract infections (UTIs, both 56.8%), and the most common symptoms were fatigue/weakness (71.7%) and pain (64.6%). With regard to HRU during follow-up, 37.4% required lithotripsy, 31.3% required ureteroscopy, and 9.6% required nephrolithotomy. PH1-related hospitalizations and emergency / urgent care visits were noted for 84.0% and 81.6% of patients, respectively. Conclusions: The current study demonstrated that patients with PH1 across various stages of kidney disease exhibited a substantial clinical burden, including kidney stones, UTIs, fatigue/weakness, and pain, and required frequent HRU, including kidney stone procedures, hospitalizations, and emergency visits. These findings highlight the significant morbidity and HRU burden in patients with PH1.